Structural characterization and alleviation on osteoporotic of polysaccharide purified from Psidium guajava L. leaves - Meng Meng; Rui Zhang; Fang Ning; Ying Sun; Yinyin Feng; Xiaoyang He; Ran Han; Qinghua Liu; Huiqing Sun (Journal of Agriculture and Food Research)
Psidium guajava L. leaves contain various bioactive components have been utilized in traditional medicine for the treatment of diseases. A novel acidic polysaccharide (GLP) was extracted and purified from Psidium guajava L. leaves, an underutilized by-product of guava processing. GLP. The molecular weight of GLP was found to be 1.723 × 103 kDa and mainly consists of arabinose, galactose, galacturonic acid and rhamnose using high performance liquid chromatography, ion chromatography, methylation analysis and nuclear magnetic resonance techniques. Key glycosidic linkages such as →3)-β-D-Galp-(1→, →3,4)-β-D-GalpA-(1→, and →3)-α-L-Araf-(1 → . were identified. In a retinoic acid-induced mouse model of osteoporosis, GLP administration significantly improved trabecular bone microarchitecture by increasing bone volume fraction, trabecular number, and thickness, while decreasing trabecular separation. Additionally, GLP markedly reduced serum levels of bone turnover markers (ALP, OC, TRACP) and pro-inflammatory cytokines (IL-6, IL-2, TNF-α). Furthermore, GLP modulated gut microbiota composition, enhancing the relative abundance of beneficial genera such as Lachnospira, Oscillospiraceae, and Dubosiella. These findings suggest that GLP not only modulates bone metabolism and inflammation but also may serve as an innovative natural therapeutic agent or functional food ingredient for the prevention and management of osteoporosis, highlighting the potential of valorizing guava leaf by-products in industrial applications.